La population immigrante est-elle plus à risque d’accidents du travail? Une analyse basée sur des données administratives au Québec - Jaunathan Bilodeau; Martin Lebeau; Marc-Antoine Busque; Daniel Côté (Perspectives Interdisciplinaires sur le Travail et la Santé)
The integration of immigrants into the Quebec labour market raises significant issues regarding workplace safety. The aim of this article is to (1) compare the risk of all accepted work accidents and serious accepted accidents between immigrants and non-immigrants in Quebec, and (2) examine differences in accident risk by occupational category and sex. An unprecedented matching of 3 administrative databases identified 9,783 immigrants among the 82,704 accepted accident cases in 2016. Negative binomial regressions reveal that immigrants admitted for less than five years face a higher risk of accidents compared to non-immigrants. Analyses of serious accidents and models stratified by occupational category and sex further nuance the results. This article underlines the importance of considering the issue of work-related accidents among immigrants from an intersectional perspective and offers suggestions as to which groups should be prioritized for intervention.